PANDANGAN IBN ‘ARABî TENTANG AL-QUR’AN SEBAGAI PENGHIMPUN - Wahyudi, Chafid (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2015)
The leaders and observers disagree about sufism narated by Ibn ?Arabî. Some parties considered him as a sufi who does not rely on the Koran, but others actually had put him always associated with the Koran. Although Ibn ?Arabî considered not to rely on the Koran, he claimed that the knowledge gained is through the ?opening? or ?disclosure? (fath, kashf) with respect to the actual meaning of the Koran. Ibn ?Arabî wrote, We are not quoting the words of the philosopher at all, nor the words of others. What we argue in this book and all our other books are what is given through Kashf and dictated by al-Haqq. Based on this claim, the authors try to lift the view of Ibn ?Arabî on the Koran